Review of Multi-Person Exposure Calls to a Regional Poison Control Center - Morgan, Brent W. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2010)
OBJECTIVE: Poisoning events, including exposures to hazardous materials, can involve multiple victims. Regional poison centers often are contacted in such events involving multiple victims. METHODS: We searched our poison center database over a nine-year time period for all calls involving a poisoning event in which more than two people were exposed to the same substance. We then matched each product to the generic category used by the National Poison Data System. We analyzed this data to find the most frequent substances reported as primary substances in the multiple exposures. RESULTS: We identified 6,695 calls between 2000 and 2008 that had more than two people exposed to the same substance. In these calls, 25,926 people were exposed (3.6% of the 715,701 human exposure calls for this period). These calls involved 64 of the 67 NPDS substance group codes. Some substances were much more commonly involved than others. The top three categories causing the most exposures were Fumes/Gases/Vapors, Food Products/Food Poisoning and Pesticides. Of the patients exposed, 69.4 % were not followed due to minimal effects possible or judged as nontoxic, 0.3% had major effects, 8.6% had no effects, and 9.3% had minimal to moderate effects. Eight people expired. CONCLUSION: Fumes, gases, and vapors make up the majority of multi-exposure calls. The overall mortality from multi-exposures, based on our data, is low. Analysis of these calls can help poison centers better understand these events and direct training.